United Kingdom Myeloma Forum position statement on the use of consolidation and maintenance treatment in myeloma. (27th March 2014) - Rabin, N.; Lai, M.; Pratt, G.; Morgan, G.; Snowden, J.; Bird, J.; Cook, G.; Bowcock, S.; Owen, R.; Yong, K.; Wechalaker, A.; Low, E.; et al.
Summary: Therapeutic advances and the availability of novel agents have significantly improved outcomes in myeloma; yet, it remains incurable and strategies to improve survival continue to be sought. One approach is to prolong the duration of response and increase progression‐free survival (PFS) through consolidation or maintenance treatment with regimens that have low toxicity profiles, and do not negatively impact on quality of life. Data from several studies with thalidomide, lenalidomide and bortezomib consistently show improvements in response and PFS, although results have still to be confirmed with respect to overall survival (OS). Despite the promising data, the optimal use of consolidation and maintenance treatment in terms of regimen, dose and duration has yet to be defined. Given the evidence to date, the UK Myeloma Forum believes that both maintenance and consolidation therapy should be considered as treatment options for patients with myeloma. Patients should be encouraged to enrol in clinical studies. This document reviews the current position of maintenance and consolidation for patients with myeloma treated in the UK.